Backache could be an indication of multiple myeloma: An unusual case report (Bangladesh Journal of Medical Science, 2018)
Unusual presentation of multiple myeloma (MM) poses a diagnostic dilemma. The objective of this case report is to document the unique presentation of MM and to highlight the importance of backache which could be the only indicator for the diagnosis of MM. Although a history of trauma in the past is present in this case, but there is no molecular basis/evidence to declare trauma as a risk factor for MM. It can be concluded that the patients with backache should be thoroughly investigated to rule out any possibility of malignant disease process.Bangladesh Journal of Medical Science Vol.17(2) 2018 p.311-315